2020
DOI: 10.1155/2020/6973636
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Dichloroacetate and Atorvastatin Regulates Excessive Proliferation and Oxidative Stress in Pulmonary Arterial Hypertension Development via p38 Signaling

Abstract: Pulmonary arterial hypertension (PAH) is a lethal disease generally characterized by pulmonary artery remodeling. Mitochondrial metabolic disorders have been implicated as a critical regulator of excessively proliferative- and apoptosis-resistant phenotypes in pulmonary artery smooth muscle cells (PASMCs). Dichloroacetate (DCA) is an emerging drug that targets aerobic glycolysis in tumor cells. Atorvastatin (ATO) is widely used for hyperlipemia in various cardiovascular diseases. Considering that DCA and ATO r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
(67 reference statements)
5
8
0
Order By: Relevance
“…We further found that the level of the macrophage biomarker CD68 was reduced in the lung tissue of MCT-induced rats after DON treatment, indicating reduced pulmonary macrophage infiltration in DON group rats. This is consistent with the findings of previous studies, in which extensive infiltration of macrophages around the pulmonary perivascular region was observed in various animal models ( 45 , 46 ). More importantly, the findings suggested that M2-macrophage activation plays a more predominant role in PAH development than M1-macrophage activation via regulation of profibrotic and proinflammatory effects ( 11 ).…”
Section: Discussionsupporting
confidence: 94%
“…We further found that the level of the macrophage biomarker CD68 was reduced in the lung tissue of MCT-induced rats after DON treatment, indicating reduced pulmonary macrophage infiltration in DON group rats. This is consistent with the findings of previous studies, in which extensive infiltration of macrophages around the pulmonary perivascular region was observed in various animal models ( 45 , 46 ). More importantly, the findings suggested that M2-macrophage activation plays a more predominant role in PAH development than M1-macrophage activation via regulation of profibrotic and proinflammatory effects ( 11 ).…”
Section: Discussionsupporting
confidence: 94%
“…The typical example is “the Warburg effect” or aerobic glycolysis. Glucose consumption and lactate production induced by hypoxia or by the Warburg effect are reversed by DCA, and these results agree with several studies [ 18 , 19 ]. In addition, a decrease in lactate production also reduces acidosis, which is involved in tumor progression [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…The pathological mechanism of HPH is very complicated. Consistent with network analysis, previous studies have demonstrated that the development of pulmonary hypertension is highly related to oxidative stress ( Mikhael et al, 2019 ; Li et al, 2020 ; Türck et al, 2020 ). Our preliminary experiments show that DSY has no effect on PH induced by monocrotaline (results are not shown), but is effective for HPH.…”
Section: Discussionsupporting
confidence: 80%